Efektivitas Sistem Informasi Manajemen Baznas (Simba) dalam Penyusunan Laporan Keuangan di Wilayah Bone Soppeng Wajo (Bosowa) Sulawesi Selatan - Azizah, Andi Tenri Gading Nurul; Abdulahanaa; Muhammad Yamin (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
This research described the effectiveness of using a website-based information management system in Baznas in the Bone, Soppeng, Wajo (BOSOWA) region, South Sulawesi. The aim of the research was to analyze in depth the effectiveness of using Simba in preparing Baznas financial reports through four indicators, namely target achievement, ability to adapt to change, job satisfaction and responsibility. The research methodology used was qualitative, while the data collection techniques included observation, interviews and documentation. The research results showed that the use of Simba in preparing financial reports at Baznas BOSOWA was quite effective. It was due to the optimization of the use of the Simba application which made it easier to manage zakat, infaq and alms (ZIS) activities, especially in the financial reporting aspect